The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1984
DOI: 10.1177/106002808401800510
|View full text |Cite
|
Sign up to set email alerts
|

Injectable Ketoprofen VS. Acetylsalicylic Acid for the Relief of Severe Cancer Pain: A Double-Blind, Crossover Trial

Abstract: Thirty-six patients suffering from severe pain due to bone involvement from cancer participated in an analgesic study that compared single doses of ketoprofen 100 or 400 mg iv or injectable acetylsalicylic acid 1 g. A double-blind, balanced incomplete block design was adopted, in which each patient received two of the three test treatments, with an interval of 24 hours. Ketoprofen 400 mg proved significantly superior to 100 mg of the same drug, and was superior to 1 g of the acetylsalicylic acid derivative in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

1988
1988
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 6 publications
0
15
0
Order By: Relevance
“…We screened 5991 publications, of which 43 met the inclusion criteria after full‐text review ( Figure ) . We excluded 30 studies (Supporting Information, S4).…”
Section: Resultsmentioning
confidence: 99%
“…We screened 5991 publications, of which 43 met the inclusion criteria after full‐text review ( Figure ) . We excluded 30 studies (Supporting Information, S4).…”
Section: Resultsmentioning
confidence: 99%
“…Four studies enrolled patients with either malignant bone pain, non-bone malignant pain, or both, but results were not reported separately for bone-related and non-bone-related pain in any study. Three studies [25][26][27] examined the analgesic efficacy of NSAIDs specifically for malignant bone pain, but not for other types of malignant pain. Analgesic efficacy data were extractable from only two of these studies, but were not combinable because one was a single-dose trial [27] and the other a multiple-dose trial [25].…”
Section: Anti-inflammatory Agentsmentioning
confidence: 99%
“…Three studies [25][26][27] examined the analgesic efficacy of NSAIDs specifically for malignant bone pain, but not for other types of malignant pain. Analgesic efficacy data were extractable from only two of these studies, but were not combinable because one was a single-dose trial [27] and the other a multiple-dose trial [25]. The single-dose with ketoprofen study crossover reported a mean NSAID-induced PPID of 40% to 55% and SPID of 34% to 45%.…”
Section: Anti-inflammatory Agentsmentioning
confidence: 99%
“…Four studies enrolled patients with either malignant bone pain, non-bone malignant pain, or both, but results were not reported separately for bone-related and non-bone-related pain in any study. Three studies [25-27] examined the analgesic efficacy of NSAIDs specifically for malignant bone pain, but not for other types of malignant pain. Analgesic efficacy data were extractable from only two of these studies, but were not combinable because one was a single-dose trial [27] and the other a multiple-dose trial [25].…”
Section: Anti-inflammatory Agentsmentioning
confidence: 99%
“…Three studies [25-27] examined the analgesic efficacy of NSAIDs specifically for malignant bone pain, but not for other types of malignant pain. Analgesic efficacy data were extractable from only two of these studies, but were not combinable because one was a single-dose trial [27] and the other a multiple-dose trial [25]. The single-dose with ketoprofen study crossover reported a mean NSAID-induced PPID of 40% to 55% and SPID of 34% to 45%.…”
Section: Anti-inflammatory Agentsmentioning
confidence: 99%